Sentiment Analysis on BNI Mobile Application Review Using K- Nearest Neighbors Algorithm - Nurmakhlufi, Alfin; Arsyad , Muhammad Rafi Haidar; Mulyani , Wahyu Sri; Nugroho, Kristiawan (Sinkron : jurnal dan penelitian teknik informatika, 2024)
Advances in Science and Technology continue to evolve in response to the demands of modern times, particularly in various fields such as banking. The development of information technology has transformed the way transactions are conducted from traditional to digital, accessible flexibly through Mobile Banking. BNI has created the BNI Mobile Banking application to facilitate customers in their transactions. The objective of this study is to investigate how the use of BNI Mobile can influence the ease of customers in conducting transactions. The data collection method used in this study is the K-Nearest Neighbors method, focusing on user experience with the BNI Mobile Banking application